Assembling “Digital Literacies”: Contingent Pasts, Possible Futures - Nichols, T. Philip (2019)
In this article, we examine the historical emergence of the concept of “digital literacy” in education to consider how key insights from its past might be of use in addressing the ethical and political challenges now being raised by connective media and mobile technologies. While contemporary uses of digital literacy are broadly associated with access, evaluation, curation, and production of information in digital environments, we trace the concept’s genealogy to a time before this tentative agreement was reached—when diverse scholarly lineages (e.g., computer literacy, information literacy, media literacy) were competing to shape the educational agenda for emerging communication technologies. Using assemblage theory, we map those meanings that have persisted in our present articulations of digital literacy, as well as those that were abandoned along the way. We demonstrate that our inherited conceptions of digital literacy have prioritized the interplay of users, devices, and content over earlier concerns about technical infrastructures and socio-economic relations. This legacy, we argue, contributes to digital literacy’s inadequacies in addressing contemporary dilemmas related to surveillance, control, and profit motives in connective environments. We propose a multidimensional framework for understanding digital literacies that works to reintegrate some of these earlier concerns and conclude by considering how such an orientation might open pathways for education research and practice.